2003
DOI: 10.1080/02652030310001620405
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of microflora and of ochratoxin A in green coffee beans (Coffea arabica)

Abstract: Coffee is produced in tropical countries around the Equator where climatic conditions are favourable for fungal development and mycotoxin production; however, mycotoxins do not only occur in the tropical countries. The aim was to evaluate the mycoflora and possible incidence of ochratoxin A (OTA) in 60 samples of green coffee beans from Brazil. The mycological evaluation was carried out using a conventional method and the OTA was determined using sequential phenyl silane and immunoaffinity column cleanup follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 15 publications
1
28
0
6
Order By: Relevance
“…Studies conducted in Brazil have shown that the percentage of coffee samples contaminated with OTA ranges from 7.5 % to 98.8 % and the OTA levels range from 0.10 to 7.30 ng/g and from 0.10 to >100 ng/g in green and processed coffee, respectively (Table 3) (Prado et al 2000;Taniwaki et al 2003;Batista et al 2003;Martins et al 2003;Gollücke et al 2004;Almeida et al 2007;Batista et al 2009). In coffee samples from Mexico, OTA occurrence were low and the OTA level detected on green coffee samples was 0.20 ng/g, while on processed coffee, samples varied between 0.10 and 0.30 ng/g (Suárez-Quiroz et al 2004).…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies conducted in Brazil have shown that the percentage of coffee samples contaminated with OTA ranges from 7.5 % to 98.8 % and the OTA levels range from 0.10 to 7.30 ng/g and from 0.10 to >100 ng/g in green and processed coffee, respectively (Table 3) (Prado et al 2000;Taniwaki et al 2003;Batista et al 2003;Martins et al 2003;Gollücke et al 2004;Almeida et al 2007;Batista et al 2009). In coffee samples from Mexico, OTA occurrence were low and the OTA level detected on green coffee samples was 0.20 ng/g, while on processed coffee, samples varied between 0.10 and 0.30 ng/g (Suárez-Quiroz et al 2004).…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 98%
“…Coffee is extensively consumed worldwide and Brazil is the major coffee bean producer and exporter in the world. Urbano et al (2001) and Martins et al (2003) evaluated the incidence of fungal species in coffee samples from Brazil, and among OTA-producer species were isolated A. ochraceus and A. niger. A lower frequency of A. ochraceus isolation than A. niger was observed in both studies, but the percentage of ochratoxigenic strains was higher.…”
Section: Coffee Samplesmentioning
confidence: 99%
“…Aspergillus ochraceus has been isolated from coffee samples by several authors (Urbano et al, 2001b;Taniwaki et al, 2003;Martins et al, 2003;Batista et al, 2003;Suárez-Quiroz et al, 2004) and was proposed as the major cause of OA in coffee beans (Frank, 1999). However, A. carbonarius and A. niger, capable of producing OA, have also been isolated from coffee (Téren et al, 1997;Nakajima et al, 1997;Joosten et al, 2001;Urbano et al, 2001b;Taniwaki et al, 2003;Pardo et al, 2004;Suárez-Quiroz et al, 2004), indicating that these two species are also potential sources of OA in coffee.…”
Section: Fungi Producing Ochratoxin a In Coffeementioning
confidence: 99%
“…It is the common contamination in various food and feed such as grains, fruit juice, milk, coffee and wines [2][3][4][5][6], in particular, it can be accumulated in tissues and organs of animals [7], resulting in longterm toxicity. It has been clearly demonstrated that OTA exposure can cause several kinds of toxicity including nephrotoxic, teratogenic, and immunotoxic effects in mammalian [8,9].…”
Section: Introductionmentioning
confidence: 99%